ANALISIS PENGARUH HARGA, PELAYANAN, ATMOSFER KENYAMANAN, KERAGAMAN PRODUK, DAN DESAIN TOKO TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI KASUS PADA GARDENA DEPARTMENT STORE) - Bahri, Bahri; Muttaqiyathun, Ani (Jurnal Fokus Manajemen Bisnis, 2011)
One effort that may be company performed to improve the customer is to determine the price, service, comfort atmosphere, the diversity of products and store design is good and interesting. The purpose of this study, to examine the influence of price, service, atmosphere convenience, product diversity, and store design on consumer purchase decisions either partially or simultaneously. Techniques used in sampling in this study was purposive sampling. The number of samples used as much as 100 samples.Methods of analysis used to test the hypothesis that F Test and t-test. Measurement instruments used for the five independent variables are qualified validity and reliability.The results showed that the partial test results all independent variables (price, service, atmosphere convenience, product diversity, and store design) significantly influence consumer purchasing decisions. And test results together (F test) showed that all variables independent (X) has positive and significant impact on consumer purchasing decisions (Y).